The Limits of Director and Notary Liability in Cases Involving Forged Documents - Fatimah, Dyah Ayu Putri; Deni, Fitra; Harlina, Indah (Jurnal Ilmu Hukum Kyadiren, 2026)
The increasing use of forged documents in the establishment of a Limited Liability Company raises significant concerns regarding the legal liability of directors and the vulnerable position of notaries. This study aims to analyze the legal responsibility of directors for forging signatures in supporting documents for the deed of establishment and to examine the scope of legal protection afforded to notaries. This research employs a normative legal method, utilizing statutory and case-based approaches. The findings reveal that directors may incur both criminal and civil liability for fulfilling the elements of forgery and breaching their fiduciary duties, whereas notaries who act in good faith and exercise due diligence are entitled to legal protection. In conclusion, there is a need to clarify the boundaries of liability and to strengthen verification mechanisms in order to ensure legal certainty and justice.